2019
DOI: 10.1111/1469-8676.12625
|View full text |Cite
|
Sign up to set email alerts
|

European social anthropology in 2018: an increasingly recursive public

Abstract: In 2018, social anthropology finds itself increasingly concerned with its technical, legal and political conditions of possibility. The long‐term effects of austerity, financialisation and the technological transformation of media on teaching, research and publishing have led to intense struggles over the labour and property regimes underpinning the discipline. In responding to these challenges, anthropologists seem to be re‐conceptualising their own personhood and labour through the diverse conceptualisations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 148 publications
(152 reference statements)
0
5
0
Order By: Relevance
“…The study of kinship found new life as the anthropology of new reproductive technologies, and the anthropology of knowledge has been reincarnated in scientific laboratories. In a vicious circle, this monochromatic dramaturgy only reinforces the domaining tendency already present and long critiqued (McKinnon and Cannell 2013; see also Bear et al 2015;Hughes 2019;Yanagisako and Delaney 1994). It is as if we have at once dispensed with the possibility of grasping a multidimensional totality (unless at the 'seamless' global scale ;Candea 2007: 170), and yet we have been projecting a new sense of reified to-tv tality, only now conjuring it in closed quarters, where one dimension overpowers all others.…”
Section: Follow the Relationshipmentioning
confidence: 90%
“…The study of kinship found new life as the anthropology of new reproductive technologies, and the anthropology of knowledge has been reincarnated in scientific laboratories. In a vicious circle, this monochromatic dramaturgy only reinforces the domaining tendency already present and long critiqued (McKinnon and Cannell 2013; see also Bear et al 2015;Hughes 2019;Yanagisako and Delaney 1994). It is as if we have at once dispensed with the possibility of grasping a multidimensional totality (unless at the 'seamless' global scale ;Candea 2007: 170), and yet we have been projecting a new sense of reified to-tv tality, only now conjuring it in closed quarters, where one dimension overpowers all others.…”
Section: Follow the Relationshipmentioning
confidence: 90%
“…The rise of the so‐called ‘neoliberal turn’ in academia has been remarked on in recent annual surveys of anthropological publishing in both Europe and the USA (Hughes 2018; Muehlebach 2013). Identified and theorised by Strathern (2000), ‘audit culture’ now dominates the European university.…”
Section: Authoritarianism Austerity and Audit: The Fraying Of The Acmentioning
confidence: 99%
“…A significant number of articles published in 2019, within the rubric of anthropology, inhabit that borderland that anthropology shares with neighbouring social sciences: with human geography (Saxer and Andersson 2019; Brachet and Scheele 2019; Gardini 2019; Saxer 2019; Gohain 2019; Schweitzer and Povoroznyuk 2019; Luo et al 2019; Fradejas‐Garcia 2019; Andersson 2019); area studies (Goh 2019); urban studies (Civelek 2019; Kobi 2019); development studies (Green 2019); human economics (Diggins 2019; Pied 2019; Henig 2019); and sociology (Miller 2019). Geoffrey Hughes, in his 2018 survey of European anthropology in this journal (Hughes 2018), referred to the rise of what he called ‘meta‐anthropology’, breaking down traditional boundaries between academic knowledge production and knowledge practices, both in the field and in wider political economies, a development he cautiously welcomed as prefiguring a more secure future for the discipline in the age of audit and concrete accountability for so‐called ‘deliverables’. The dangerous reverse image of this is perhaps hinted at by the shopping list of ‘anthropological’ tools or marketable value additions set out by Sausdal and Vigh (2019) referred to earlier, in their plea for the creation of an ‘anthropological’ criminology.…”
Section: Authoritarianism Austerity and Audit: The Fraying Of The Acmentioning
confidence: 99%
“…Some scholars refuse to alter their research topics, yet this can entail a lack of funding and thus detrimental consequences for their careers. Such financial predicaments are amplified amidst the contemporary conditions of the neoliberal university, wherein we are increasingly expected to perform a wide variety of tasks and are measured by our 'impact' on our field (see Hughes 2019;Stein 2018). We need to be careful and resist these dynamics in which we are pushed, and sometimes pressured, by funding agencies and policymakers.…”
Section: Providing 'Solutions'mentioning
confidence: 99%